Pengembangan Teknik Latihan Menggunakan Microsft Word Untuk Media Pembelajaran Menulis Teks Berita Bagi Peserta didik Kelas XI SMA Negeri 1 Bulakamba. - Devi, Sri (Peneliti.net, 2025)
The research utilized the Research and Development (R&D) methodology, encompassing stages such as identifying potentials and issues, data collection, product design, design validation, and design revision. The study involved 72 students from classes XI 1 and XI 3, employing observation, interviews, questionnaires, and documentation for data gathering. Validation results indicated that the content aspect, comprising seven components, received an appropriate score of 87.21. The feasibility of presentation, assessed through three components, scored 91.25, while the linguistic aspect, evaluated with two components, scored 93.5. The graphic aspect, involving five components, received a score of 89. The total score for the suitability of Microsoft Office Word in teaching news text writing with practice techniques to class XI students at SMA Negeri 1 Bulakamba was 360.96, suggesting that the learning media is suitable for adoption with minor revisions.